The role of information in pharmaceutical advertising: Theory and evidence - Kelli Marquardt; Conor Ryan (Federal Reserve Bank of Chicago, 2023)
This paper theoretically and empirically examines the role of information in the practice of pharmaceutical detailing (promotional interactions between drug representatives and physicians). We start with a theoretical framework in which pharmaceutical firms target detailing visits to physicians who potentially learn about drug quality and prescribe it to their patients. We derive several predictions about the role of information in these visits, which we then test empirically using Medicare Part D prescriptions and pharmaceutical detailing visit data. We find there is little empirical evidence to support learning as a primary mechanism of detailing visits and, in fact, document strong evidence to the contrary.
Keywords: I1; D8; L0; M3; 330; pharmaceutical advertising; physician learning